Analysis of Early Breastfeeding Initiation for Newborns in Palu City - Ayu Lestari; Shindi Karmila Adam; Jamaludin M Sakung (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Early breastfeeding initiation is a critical intervention to reduce neonatal mortality and increase exclusive breastfeeding However, its implementation in RSIA Tinatapura Palu is still not optimal. This study aimed to assess the provision of early initiation of breastfeeding in newborns and identify the factors that inhibit it at Tinatapura Mother and Child Hospital, Methods: This study uses a qualitative method with a descriptive approach, which aims to conduct in-depth interviews through data collection from various sources of information. Results: This study found that implementation of early breastfeeding initiation at RSIA Tinatapura Palu was not optimal, with the majority of mothers reporting no IMD Key barriers included low maternal knowledge about IMD, postpartum maternal and infant health conditions, inconsistent hospital policies such as mother-infant separation after delivery (especially for sectio caesarean/premature cases) and flexibility in formula feeding without medical indication, and inadequate support from health workers, including lack of education and a tendency to recommend While hospitals claim to provide training and education, there is a gap between policy and practice on the Conclusion: The implementation of early breastfeeding initiation in RSIA Tinatapura Palu is still not running. Structured interventions are needed in the form of clear IMD protocols, increased education for mothers and families, and ongoing training for health workers to ensure consistent and standardized IMD.